ANALISIS POLA PERSEBARAN MASJID MENGGUNAKAN METODE NEAREST NEIGHBOR ANALYSIS DI KECAMATAN SERENGAN KOTA SURAKARTA - Moh Ali Ma'sum (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
Serengan as one of the sub-districts with a majority Muslim population certainly respects and maintains the sanctity of the mosque building. The evidence is that the growth rate of mosque construction has increased, but an increase in the number is expected to result in an uneven distribution of the mosque. Because of this, the researchers studied this with the aim of a) knowing the distribution of mosques in the Serengan sub-district, Surakarta City, and b) applying the GIS function to analyze the distribution of mosques in the Serengan sub-district, Surakarta City. This research is a type of descriptive research with a quantitative approach with a distribution pattern analysis technique using Nearest Neighbor Analysis (nearest neighbor analysis). The results of this study found that the distribution of mosques, in general, has a uniform pattern (dispersed pattern) with an index of 18.52 out of a total of 51 mosques.